Antioxidative Effects of Lemon Oil and its Components on Copper Induced Oxidation of Low Density Lipoprotein - Graßmann, Johanna; Schneider, Dagmar; Weiser, Dieter; Elstner, Erich F. (Arzneimittelforschung, 2001)
Oxidation of low density lipoprotein (LDL) has been implicated in atherogenesis since several years. Therefore many researchers are looking for potent antioxidants which are able to inhibit LDL-oxidation and thus lower the risk for atherosclerosis. In particular several flavonoids have been investigated for their anti-oxidant capacity and it was shown that many factors influence the ability of flavonoids to retard LDL-oxidation, among others their lipophilic character. Since essentail oils and some of their components which are highly lipophilic, have been shown to possess antioxidant properties, their effects on copper-induced LDL-oxidation were analysed. Plasma was incubated with different terpenoid substances and subsequently the LDL was isolated. It could be demonstrated that the terpenoids were enriched in LDL after incubation with plasma. To follow the kinetics of copper induced LDL-oxidation formation of conjugated dienes as well as loss of tryptophan fluorescence were measured. Furthermore the anti-oxidants α -tocopherol, β-carotene and lycopene were quantified in LDL. It could be shown that particularly lemon oil and one of its components, γ-terpinene, are efficiently slowing down the oxidation of LDL. This effect is independent of α-to-copherol stability in LDL, whereas the loss of carotenoids during oxidation is strongly retarded.
Keywords: Antioxidants; Essential oils; Lemon oil, antioxidative effect; Low density lipoprotein, oxidation; Terpenoids; Terpinene